2020
DOI: 10.3390/f11040420
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do Three Tree Species Adapt to the Urban Environment in Guangdong-Hongkong-Macao Greater Bay Area of China Regarding Their Growth Patterns and Ecosystem Services?

Abstract: It is predicted that global change combined with urbanization will impact increasingly on the society and terrestrial ecosystem in the Guangdong-Hongkong-Macao Greater Bay Area of China (GBA). In this context, the cities in GBA began to plant a variety of urban trees since 2000 which are considered to play an important role in fixing carbon, improving air quality, reducing noise and providing other ecosystem services. However, data on the growth patterns and ecosystem services of the planted trees remains scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Foshan, an inland city in GBA, was famous for its rapidly developing economy, which relied mainly on the manufacturing industry (Lu et al, 2005). As CUA with restricted areas might face both economic and environmental stress, Foshan was transferring part of the industry to SUA and especially UFA (Zhang et al, 2020). Taking into account this phenomenon and becoming a national forest city in 2018 (Zhang et al, 2020), it could be confirmed that Foshan had an increasing demand for forest construction as urban forests were highly expected to provide various ecosystem services such as reducing noise, purifying air quality, and improving environmental quality.…”
Section: Current Circumstances Of the Three Surveyed Citiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Foshan, an inland city in GBA, was famous for its rapidly developing economy, which relied mainly on the manufacturing industry (Lu et al, 2005). As CUA with restricted areas might face both economic and environmental stress, Foshan was transferring part of the industry to SUA and especially UFA (Zhang et al, 2020). Taking into account this phenomenon and becoming a national forest city in 2018 (Zhang et al, 2020), it could be confirmed that Foshan had an increasing demand for forest construction as urban forests were highly expected to provide various ecosystem services such as reducing noise, purifying air quality, and improving environmental quality.…”
Section: Current Circumstances Of the Three Surveyed Citiesmentioning
confidence: 99%
“…However, UFA showed the highest diversity and tree species density, implying a recent focus on this area. Furthermore, as CUA and SUA were already occupied with various enterprises, it was necessary to transfer part of the industry to UFA and together with which, the forest construction obtained enhanced investment (Zhang et al, 2020). Hence, to introduce different tree species in CUA and SUA could increase their diversity to optimize the ecosystem services and achieve balanced development between the three areas.…”
Section: Probable Improvement From Ecological Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of urban tree species for urban greening should cautiously take tree's adaption to the local environment into account 45,48 . Meanwhile, considering the surge of global change, how well trees responded to extreme climatic events should be profoundly evaluated for their conservation and management in the future 22 . In cities such as Guangzhou with rapid increasing urbanization together with a trend of rising temperature and reduced precipitation, the introduced or selected urban tree species were better to cope with drought positively to avoid high mortality together with economic loss.…”
Section: Strategies Of Fine Root Development At Both Vertical and Hor...mentioning
confidence: 99%
“…Particularly under drought stress, trees could dynamically adjust their investment in root growth from different perspectives, such as increasing the growth at vertical or horizontal levels, and accelerating root turnover rates 20,21 . For urban trees, the below-ground development patterns could reflect tree's adaption adequately as this could be the most efficient and practical way of coping with harsh surroundings and restricted water supply 22 . Therefore, to evaluate the adaption of two potentially-introduced tree species in Guangzhou, we launched a drought-simulation experiment and measured their above-and below-ground growth, including the development of tree height, diameter in breast height, crown areas, and fine root biomass at different directions.…”
mentioning
confidence: 99%